Nilai-nilai Agama dan Moral pada Pembelajaran Teks Nonfiksi Siswa SD Inpres Pallangga Kabupaten Gowa - Wulandari, Erika; Mayong, Mayong; Hajrah, Hajrah (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study examines the analysis of religious and moral values ​​in nonfiction text learning at Pallangga Elementary School, Gowa Regency. This study aims to describe the religious and moral values ​​contained in nonfiction text learning at Pallangga Elementary School, Gowa Regency. This study used a qualitative method with a descriptive approach. Data collection techniques included observation, interviews, and documentation. The results show that teachers actively instill religious values ​​by selecting texts containing stories of religious figures and relating them to students' real lives. Religious values ​​such as faith, honesty, patience, and responsibility are the main focus in developing students' religious character. In addition, moral values ​​such as cooperation, discipline, and mutual respect are also taught through a contextual and creative approach. Students' responses to this learning were positive, and they were able to internalize these values ​​in their daily behavior. Learning nonfiction texts contributes to strengthening character values ​​through the integration of religious and contextual stories.